Decision Support System Assessing Feasibility Taekwondo Athlete (UPN “VETERAN” Yogyakarta) - Nur Heri Cahyana; Fachrizal Herdiansyah; Rifki Indra Perwira (SENATIK STT Adisutjipto, 2019)
Indonesian taekwondo athlete's achievements have improved because he managed to win several medals in international championships. Being a taekwondo athlete requires a willingness, discipline, good physical condition, experience, mental endurance, unyielding spirit, and proper posture. The assessment process is still done manually by asking taekwondo for their availability in the match; therefore, it requires a decision support system to measurement of participants (taekwondoin).   Decision support is a way to provide problem-solving skills and be able to support the work of a coach in solving problems by giving suggestions towards certain decisions. The purpose of Simple Additive Weighting is to determine the feasibility of taekwondoin selection to become an athlete on the championship team. Dynamic criteria allow adding the criteria needed for coaches and managers. Coaches and managers also can refine taekwondo by adding the required criteria to the agreed additional criteria. The result of this paper is application can give the decision of athletes who deserve to enter the match team. To facilitate managers and coaches in screening the best athletes. The validation test results obtained 85% compatibility between the selection results in the application and manual calculations.